Political Science as a Social Science of Power, Authority, and Legitimacy - Arditya Prayogi; Riki Nasrullah; Novianto Ade Wahyudi; Luthfia Rosidin (PAPSEL RESEARCH AND CONSULTANT, 2026)
Political science is often understood narrowly as the study of the state and formal institutions, yet political practices also occur within social relations that shape power, authority, and legitimacy outside the state arena. This article aims to reformulate political science's position as a social science by mapping the main objects of study, comparing four analytical approaches, and emphasizing the importance of empirical rigor in political explanation. This article was written using a qualitative design based on literature studies, with data sources consisting of relevant books and scientific articles. The author then applies thematic-conceptual analysis through repeated readings, coding key concepts, and compiling thematic syntheses. The results of the study indicate that political science within the social science framework sees four approaches: institutionalism, which highlights the role of rules and incentives; the behavioral/rational approach, which emphasizes actor choices and strategies; political economy/structuralism, which places material inequality as a determinant of power configurations; and discourse constructivism, which explains how meaning and